High‐Resolution 3D Proton MRI of Hyperpolarized Gas Enabled by Parahydrogen and Rh/TiO2 Heterogeneous Catalyst. Issue 37 (7th July 2014) - Kovtunov, Kirill V.; Barskiy, Danila A.; Coffey, Aaron M.; Truong, Milton L.; Salnikov, Oleg G.; Khudorozhkov, Alexander K.; Inozemtseva, Elizaveta A.; Prosvirin, Igor P.; Bukhtiyarov, Valery I.; Waddell, Kevin W.; Chekmenev, Eduard Y.; Koptyug, Igor V.
Abstract Invited for the cover of this issue is the group of Igor V. Koptyug at International Tomography Center; Valery I. Bukhtiyarov at Boreskov Institute of Catalysis of Russian Academy of Science; and Eduard Y. Chekmenev and Kevin W. Waddell at Vanderbilt University Institute of Imaging Science, Nashville. The image depicts the synthesis of hyperpolarized propane gas using parahydrogen‐induced polarization on the surface of a heterogeneous solid‐phase Rh catalyst, which enables very high‐resolution 3D magnetic resonance imaging of flowing propane gas. Read the full text of the article at 10.1002/chem.201403604.